Adaptive routing for layer-2 load balancing in data center networks - Kanagavelu, Renuga (2013)
With the Internet boom over the last decade, large scale Data Centers are rapidly increasing in capacity and numbers to meet the ever increasing demand for bandwidth. There is a trend of deploying a large number of commodity layer-2 Ethernet switches in Data Centers. However, the existing Spanning Tree Protocol (STP) used in the traditional Ethernet networks becomes inefficient for Data Centers as it underutilizes the resources due to the lack of multipath capability leading to poor bandwidth utilization. In this paper we develop a layer-2 load balancing framework with a multi-path forwarding mechanism which balances the load across the network, thereby reducing the occurrence of congestion that leads to efficient utilization of the bi-section bandwidth in Data Centers. The proposed framework has several important features: 1) It provides adaptive multi path forwarding compatibility in layer-2 Ethernet switched networks to efficiently spread the load in adaption to changing load conditions. 2) It improves the bi-section bandwidth utilization in Data Center networks. 3) It is capable of achieving load balancing at the layer-2 level and 4) It ensures effective traffic redistribution upon link failures. We demonstrate the effectiveness of the proposed mechanism through simulation results.